2019
DOI: 10.1001/jamacardio.2019.3511
|View full text |Cite
|
Sign up to set email alerts
|

Association of Frailty With 30-Day Outcomes for Acute Myocardial Infarction, Heart Failure, and Pneumonia Among Elderly Adults

Abstract: IMPORTANCEThe addition of a claims-based frailty metric to traditional comorbidity-based risk-adjustment models for acute myocardial infarction (AMI), heart failure (HF), and pneumonia improves the prediction of 30-day mortality and readmission. This may have important implications for hospitals that tend to care for frail populations and participate in Centers for Medicare & Medicaid Services value-based payment programs, which use these risk-adjusted metrics to determine reimbursement.OBJECTIVE To determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
123
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 136 publications
(139 citation statements)
references
References 33 publications
5
123
1
4
Order By: Relevance
“…Previous studies have shown frailty, independent of age, to correlate with poorer outcomes for respiratory diseases such as pneumonia. 24,25 We demonstrated that increasing frailty score positively correlated with poorer outcomes in those with COVID-19. Further studies should aim to determine whether this link remains after accounting for age and other specific comorbidities.…”
mentioning
confidence: 75%
“…Previous studies have shown frailty, independent of age, to correlate with poorer outcomes for respiratory diseases such as pneumonia. 24,25 We demonstrated that increasing frailty score positively correlated with poorer outcomes in those with COVID-19. Further studies should aim to determine whether this link remains after accounting for age and other specific comorbidities.…”
mentioning
confidence: 75%
“…The largest study of frailty in critical illness showed that frail adults were twice as likely to die in the hospital and within 1 year than the non-frail [32,33]. Frailty is not only independently associated with hospitalizations and mortality in adults with pneumonia but also appears to have a synergistic effect on respiratory function along with lung disease [34,35] Previous studies have found that age, cardiovascular disease, and cerebrovascular disease were predictive of fatal outcomes [24]. In our study, comorbidities were not associated with higher risk of severe disease in either univariate or multivariate analyses including frailty.…”
Section: Discussionmentioning
confidence: 99%
“… 3 Pneumonia is also a common reason for hospital readmission, particularly among older adults, who often experience a functional decline during the index admission. 4 , 5 , 6 , 7 , 8 Studies have identified an inverse association between functional status and risk of hospital readmission. 9 , 10 , 11 , 12 In addition, there is a growing body of literature on the detrimental effects of acute care hospitalization on functional independence.…”
Section: Introductionmentioning
confidence: 99%